Protection Spell : Poems - Givhan, Jennifer (Book collections on Project MUSE., 2017)
In Protection Spell, Jennifer Givhan explores the guilt, sadness, and freedom of relationships: the sticky love that keeps us hanging on for no reason other than love, the inky place that asks us to continue revising and reimagining, tying ourselves to this life and to each other despite the pain (or perhaps because of it). These poems reassemble safe spaces from the fissures cleaving the speaker's own biracial home and act as witnesses speaking to the racial iniquity of our broader social landscape as well as to the precarious standpoint of a mother-woman of color whose body lies vulnerable to trauma and abuse. From insistent moments of bravery, a collection of poems arises that asks the impossible, like the childhood chant that palliates suffering by demanding nothing less than magical healing:sana sana colita de rana, si no sanas hoy, sanas mañana(the frog who loses his tail is commanded to grow another). In the end, Givhan's verse offers a place where healing may begin. --Publisher description.